Plant Secondary Metabolites—Missing Pieces in the Soil Organic Matter Puzzle of Boreal Forests - Adamczyk, Bartosz; Adamczyk, Sylwia; Smolander, Aino; Kitunen, Veikko; Simon, Judy (My University, 2018)
Processes underlying soil organic matter (SOM) transformations are meeting growing interest as SOM contains more carbon (C) than global vegetation and the atmosphere combined. Therefore, SOM is a crucial element of the C cycle, especially in ecosystems rich in organic matter, such as boreal forests. However, climate change may shift the fate of this SOM from C sink into C source, accelerating global warming. These processes require a better understanding of the involved mechanisms driving both the C cycle and the interlinked nitrogen (N) cycle. SOM transformations are balanced by a network of interactions between biological, chemical and physical factors. In this review, we discuss the findings of the most recent studies to the current state of knowledge about the main drivers in SOM transformations. We focus on plant-derived secondary metabolites, as their biochemical traits, especially interactions with soil microbial communities, organic N compounds and enzymes make them potential regulators of SOM decomposition. However, these regulatory abilities of plant-derived compounds are not fully explored.
Keywords: entsyymiaktiivisuus; terpenes; metsämaa; enzyme activity; forest soils; tannins; terpenoids; tanniinit; terpeenit